SOCIAL MEDIA MARKETING AS A SUPPORTING TOOL FOR BRAND BUILDING AND ITS IMPACT ON CUSTOMER PURCHASE DECISION. - Muhammed Jawo (Jurnal Ilmiah Mahasiswa FEB, 2017)
Social media has brought a lot of responsiveness to both companies and individuals interacting online. Marketers nowadays are everywhere to get customers. Social media marketing and advertising is a form of internet advertising that comes with the usage of social media platforms and web sites to sell a product or service. The aim of this study is to examine social media marketing as a tool for brand building and the impacts of social media marketing on customer purchase decision. The research is qualitative (exploratory method) with the intent of generating new theory from data. The data collection technique of this study uses questionnaire, observation, and interview. The sampling technique used is purposive sampling. Credibility and dependability are in place to guarantee the trustworthiness of this study. Since the research is qualitative in nature, content analysis is used a method or technique of data analysis. The result from this study shows that almost everyone uses social media, it is a great place for brand building and things such as trust, and being present online can have significant impact on customer purchase decision.Keywords :    Social Media, Marketing, Brand Building, Impact, Customer Purchase, and Decision.